A prospective, randomized, three arm, open label study comparing the safety and efficacy of PP110, a novel treatment for hemorrhoids to preparation-H® maximum strength cream in the treatment of grade 2–3 hemorrhoids. Issue 1 (December 2015) - Klein, Ehud; Shapiro, Ron; Ben-Dahan, Jose; Simcha, Moshe; Azuri, Yosef; Rosen, Ada
Abstract Background Hemorrhoids are a common disorder that affects the quality of life of millions of people worldwide. The effectiveness of OTC medication is limited and they mainly provide symptomatic relief. In order to treat this ailment, we formulated PP110 Gel and Wipes, as a novel treatment for hemorrhoids. PP110 is based on known active ingredients with a topical film-forming agent designed to provide physical protection and prolonged tissue contact with the active ingredients. Methods PP110 Gel, PP110 Wipes and the comparator Preparation-H® were used on three patient cohorts. Treatment was administered once daily for PP110, and three-four times daily for Preparation-H®, for 14 days. Six different clinical parameters relating to common symptoms of hemorrhoids were monitored. Results PP110 Gel was significantly better than Preparation-H® in reducing bleeding (Δ = 6 %), providing pain relief (Δ = 10 %) and controlling itching (Δ = 11 %). These three parameters are considered as the most common distressing symptoms for hemorrhoids patients, demonstrating that PP110 is superior to conventional treatment. Conclusion This study demonstrated the efficacy of the PP110 Gel in treating hemorrhoids and its superiority to conventional treatments. The PP110 film-based formulation provides a slow-release mechanism and as a consequence, a prolonged therapeutic window. PP110 was both more effective in reducing hemorrhoids symptoms and more convenient to use, in that it only required application once per day.